Enhancing Durability of Hot Work Tool Steel by Duplex Treatments: A Review - Chander, Subhash; Chawla, Vikas (Asian Journal of Engineering and Applied Technology, 2016)
The abrasive wear unitedly with thermo-mechanical fatigue and plastic deformation is a critical factor of the process of failure of forging dies during the forging of components with close tolerances and not subject to further mechanical treatment. The failure rate of forging dies are also greatly influenced by the variety of the shapes of the forging and the precision with which these are made. The effective way to improve the durability of forging dies is a modification of surface properties by the constitution of layers or coatings having appropriate properties. Among huge available techniques; Plasma nitriding along with suitable coating formed by physical vapor deposition (PVD) technique; commonly known as Duplex/Hybrid treatment; is widely used, allows control of surface microstructure, enhance wear resistance, corrosion resistance and fatigue resistance. This had been noted that Duplex Treatment can increase the wear resistance of the tool/die up to 30%. The tribological behaviours of duplex treated dies in hot forging are reviewed and presented here. Some commonly used surface treatments as well as coatings in hot forging dies are given. Eventually, xperimental results obtained by various researchers could be used in theory and model developments for hot forging process and die materials at high temperatures. The review also showed the great potential in further investigations in tribology.